Structure of Francisella tularensis peptidyl-tRNA hydrolase - Clarke, Teresa E. (International Union of Crystallography, 2011)
The rational design of novel antibiotics for bacteria involves the identification of inhibitors for enzymes involved in essential biochemical pathways in cells. In this study, the cloning, expression, purification, crystallization and structure of the enzyme peptidyl-tRNA hydrolase from Francisella tularensis, the causative agent of tularemia, was performed. The structure of F. tularensis peptidyl-tRNA hydrolase is comparable to those of other bacterial peptidyl-tRNA hydrolases, with most residues in the active site conserved amongst the family. The resultant reagents, structural data and analyses provide essential information for the structure-based design of novel inhibitors for this class of proteins.